PENERAPAN METODE EKSPERIMEN MELALUI PENGENALAN WARNA : (Peneitian Tindakan Kelas Pada Kelompok A RA Pratama Tunggal Binangun) - NITA ZAKIAH (LPPM STAI DARUSSALAM LAMPUNG, 2022)
Abstract This study attempts to improve the ability of knowing color through experimental methods in the RA Pratama Tunggal Binangun. The kind of this research is collaborative Class Action Reseach. The subjects of this research are grup A RA Pratama Tunggal Binangun, consisting of 7 boys and 7 girls. Data collection method uses the sheets observation (check list) and documentation. Analysis techniques data is Quantitative research. The result showed that the ability of knowing color can increase by the experimental methods .The results of the study increased gradually, this can be seen from the data observations on pre-action, the cycle I and II . The average of percentage on pre-action is 45,83%, rising in cycle I with the percentage of 60,61%. The second cycle rises up to 81,25 %.